The impact of the education level of the members who benefit from sports businesses on their service quality expectation and perception level - Havva Demırel; Metin Yaman (Türk Spor ve Egzersiz Dergisi)
This study was carried out to identify the perceptions and expectations of the members regarding the service they receive at the businesses that offers recreational sports/fitness program and to determine whether their expectations and perceptions on the service quality differ correlating with the members' level of education. Research was carried out with 623 members, 349 women, 274 men, benefiting from sports enterprises operating in the province of Ankara. The research data were obtained using “Turkish Version of the Service Quality Assessments Scale” (SQAS-T) developed by Lam et al. and tested for the reliability and validity in Turkey by Gurbuz. In data analysis, “t” and “ANOVA” tests were used in independent groups. The expected service quality scores of the members whose education level was high school were determined to be significantly higher (p lt;0.05) only in terms of staff than the members whose education level was university, but there were no differences (p gt;0.05) in the other sub-dimensions. Also according to the education level of the members who participated in the research, statistically meaningful differences (p lt;0.05) were determined between the perceived service quality scores in terms of the staff, program, dressing rooms, and the institution. In conclusion, the level of education was determined to have an impact on expected and perceived service quality.